The role of IL-1β in the development of diabetes mellitus - Liubomyr Zaiats; Yuliya Fedorchenko; Walery Zukow (Journal of Education, Health and Sport, 2022)
Background. Currently, diabetes mellitus is the most common of all endocrine diseases with increasing tendency. The purpose of our research was to study the dynamics of serum levels of proinflammatory cytokine-IL-1β in streptozotocin-induced diabetes. Materials and methods. The experiments were performed on 88 white male Wistar rats weighing 170-210 g. Animals were divided into three groups: 1 - intact; 2 - control; 3 - experimental with a model of diabetes mellitus, which was reproduced by intraperitoneal injection of streptozotocin by “Sigma" company (USA), diluted in 0.1 M citrate buffer with a pH of 4.5, at a rate of 60 mg/kg body weight. The control group of animals received an intraperitoneal injection with an equivalent dose of 0.1 M citrate buffer solution with a pH of 4.5.